Genetic approach for yield-related traits in Indian mustard (Brassica juncea L. - Anita,; Deepak Gupta,; Anil Kumar,; Manohar Ram, (Journal of Oilseed Brassica, 2025)
India ranks fourth globally in vegetable oil production, with Indian mustard (Brassica juncea L.) as the primary oilseed crop. Despite extensive cultivation, the country faces challenges in meeting rising demand for edible oils, emphasizing the need for improved mustard productivity. This study explores the genetic relationships between seed yield and associated traits using correlation and path coefficient analysis, conducted during the rabi season of 2022-23 at SKN College of Agriculture, Rajasthan, evaluating fifty-five advanced mustard genotypes. Genotypic correlation analysis revealed that several traits, including relative water content, proline content, siliqua per plant, seeds per siliqua, siliqua length, 1000-seed weight, membrane stability index, primary branches per plant, and oil content, exhibited positive correlations with seed yield per plant. Furthermore, path coefficient analysis indicated that relative water content had the highest positive direct effect on seed yield, followed by days to maturity, seeds per siliqua, siliqua length, oil content, proline content and days to 50% flowering. These findings offer crucial insights for refining selection strategies, aimed at developing high-yielding and stress-tolerant mustard varieties to enhance overall productivity